How does the sensitivity of consumption to income vary over time? International evidence - Ergys Islamaj; M. Ayhan Kose (Koç University-TÜSİAD Economic Research Forum (ERF), 2016)
This paper studies how the sensitivity of consumption to income has changed over time as the degree of financial integration has risen. In standard theory, greater financial integration facilitates international borrowing and lending, helping to reduce the sensitivity of consumption growth to fluctuations in income. We examine the empirical validity of this prediction using an array of indicators of financial integration for a large sample of advanced and developing countries over the period 1960-2011. We report two main results. First, the sensitivity of consumption to income has declined over time as the degree of financial integration has risen. The decline has been more pronounced in advanced economies than in developing ones. Second, our regression analysis indicates that a higher degree of financial integration is associated with a lower sensitivity of consumption to income. This finding is robust to the use of a wide range of empirical specifications, country-specific characteristics and other controls, such as interest rates and outcome-based measures of financial integration. We also discuss other potential sources of the temporal changes in the sensitivity of consumption to income.
Keywords: E21; F02; F4; 330; Consumption Sensitivity; Financial Integration; Risk Sharing; Intertemporal Smoothing